Sensory cells in tunicates: insights into mechanoreceptor evolution - Anselmi, Chiara; Fuller, Gwynna K.; Stolfi, Alberto; Groves, Andrew K.; Manni, Lucia (Frontiers in Cell and Developmental Biology, 2024)
Tunicates, the sister group of vertebrates, offer a unique perspective for evolutionary developmental studies (Evo-Devo) due to their simple anatomical organization. Moreover, the separation of tunicates from vertebrates predated the vertebrate-specific genome duplications. As adults, they include both sessile and pelagic species, with very limited mobility requirements related mainly to water filtration. In sessile species, larvae exhibit simple swimming behaviors that are required for the selection of a suitable substrate on which to metamorphose. Despite their apparent simplicity, tunicates display a variety of mechanoreceptor structures involving both primary and secondary sensory cells (i.e coronal sensory cells). This review encapsulates two decades of research on tunicate mechanoreception focusing on the coronal organ's sensory cells as prime candidates for understanding the evolution of vertebrate hair cells of the inner ear and the lateral line organ. The review spans anatomical, cellular and molecular levels emphasizing both similarity and differences between tunicate and vertebrate mechanoreception strategies. The evolutionary significance of mechanoreception is discussed within the broader context of Evo-Devo studies, shedding light on the intricate pathways that have shaped the sensory system in chordates.